Encapsulation improvement and stability of ambient roll-to-roll slot-die-coated organic photovoltaic modules. (1st January 2021) - Lee, Ching-Yu; Tsao, Cheng-Si; Lin, Hua-Kai; Cha, Hou-Chin; Chung, Tsui-Yun; Sung, Yun-Ming; Huang, Yu-Ching
Abstract: The manufacture of ambient roll-to-roll (R2R) slot-die-coated organic photovoltaic (OPV) is the basis toward commercialization of OPV. The low-cost large-area encapsulation technique of stability improvement of flexible OPV module is under-investigated. The related reports on flexible encapsulation up-scaled from cell were limited. The present study develops an effective and easy encapsulation method and architecture design based on the inverted structure of ambient R2R slot-die-coated PET/ITO/ZnO/active layer/hole transport layer (HTL)/Ag. All module areas are greater than 48 cm 2 . The P3HT:PCBM and PV2000:PC71 BM adopted as active layers have the performance conversion efficiencies of modules of 1–2.2% and 4.2%, respectively. The thermally-deposited MoO3 and slot-die-coated PEDOT:PSS HTLs are used to compare the effect of HTL on T80 lifetime of the large-area flexible R2R module under the accelerated test. The accelerated stability tests regarding to different encapsulation architectures, including damp-heat and light soaking stresses, were conducted. The intrinsic and extrinsic degradation effects are analyzed. We develop the simple encapsulation design effectively suppressing the lateral ingress of oxygen and moisture. The T80 lifetime of P3HT:PCBM-based module can be improved to be 1500 h under the damp-heat test (65 °C/65% RH). The T80 lifetime of PV2000:PC71 BM-based module can last for 7000 h under the dark and ambient environment (30 °C/50 ± 20% RH).